(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the psychological and pedagogical aspects of the development of geological knowledge in students of future teachers of geography. In this, students studying natural geography, which mainly includes geological data, belong to the teenage age group, this age is distinguished from other age categories by high activity, strong envy for practical actions. In the works of psychologists, it is noted that students of this age, having a high research activity, are ready to independently organize their activities. Within this age, schoolchildren will have an increased interest in the study of nature, they willingly take part in walks, excursions, their desire to conduct experiments will be great. During this period, special attention to the organization of research and practical work, as well as the development of gaming activities, has a good effect on the formation of geological knowledge.